p-Type Schottky Contacts for Graphene Adjustable-Barrier Phototransistors - Carsten Strobel; Carlos Alvarado Chavarin; Martin Knaut; Matthias Albert; André Heinzig; Likhith Gummadi; Christian Wenger; Thomas Mikolajick (Nanomaterials, 2024)
The graphene adjustable-barriers phototransistor is an attractive novel device for potential high speed and high responsivity dual-band photodetection. In this device, graphene is embedded between the semiconductors silicon and germanium. Both n-type and p-type Schottky contacts between graphene and the semiconductors are required for this device. While n-type Schottky contacts are widely investigated, reports about p-type Schottky contacts between graphene and the two involved semiconductors are scarce. In this study, we demonstrate a p-type Schottky contact between graphene and p-germanium. A clear rectification with on–off ratios of close to 103 (±5 V) and a distinct photoresponse at telecommunication wavelengths in the infrared are achieved. Further, p-type silicon is transferred to or deposited on graphene, and we also observe rectification and photoresponse in the visible range for some of these p-type Schottky junctions. These results are an important step toward the realization of functional graphene adjustable-barrier phototransistors.